The The Utilisation of Virtual Reality as a Recovery Strategy to Stimulate Travel Intentions amidst the COVID-19 Pandemic in South Africa - Mashapa, Modjadji Matilda; Maziriri, Eugine Tafadzwa; Chuchu, Tinashe (E-Journal of Tourism, 2025)
The COVID-19 pandemic has had a devastating impact on tourism, making it difficult to predict demand. Researchers and policymakers are exploring ways to forecast tourism's recovery from the pandemic. The tourism industry could utilise virtual reality (VR) in addressing the negative effects of such pandemics. Despite the widespread interest in virtual reality, there are gaps in the empirical data on its acceptance as a recovery strategy. In particular, limited research exists on the perceptions and adoption of virtual reality tourism tools among young travellers in emerging economies such as South Africa, highlighting a regional and demographic gap in the literature. This study aims to identify the key factors that influence the acceptance of virtual reality as a recovery strategy for tourism post-COVID-19. A quantitative survey was conducted with 349 young travellers in Johannesburg, South Africa. Partial least squares structural equation modelling (PLS-SEM) using SmartPLS 3 was utilised to analyse the relationships between perceived usefulness, ease of use, credibility, attitudes, and actual use of virtual reality while the sample profile was generated through SPSS 26. The findings revealed a strong association between attitudes toward using virtual reality for travel planning and the intention to adopt virtual reality for identifying travel destinations.